Photobiomodulation Therapy on the Guided Bone Regeneration Process in Defects Filled by Biphasic Calcium Phosphate Associated with Fibrin Biopolymer - Della Coletta, Bruna Botteon; Jacob, Thiago Borges; Moreira, Luana Aparecida de Carvalho; Pomini, Karina Torres; Buchaim, Daniela Vieira [UNESP]; Eleutério, Rachel Gomes; Pereira, Eliana de Souza Bastos Mazuqueli; Roque, Domingos Donizeti; Rosso, Marcelie Priscila de Oliveira; Shindo, João Vitor Tadashi Cosin; Duarte, Marco Antônio Húngaro; Alcalde, Murilo Priori; et al. (MDPI, 2021)
The aim is to evaluate the effects of photobiomodulation therapy (PBMT) on the guided bone regeneration process (GBR) in defects in the calvaria of rats filled with biphasic calcium phosphate associated with fibrin biopolymer. Thirty male Wistar rats were randomly separated: BMG (n = 10), defects filled with biomaterial and covered by membrane; BFMG (n = 10), biomaterial and fibrin biopolymer covered by membrane; and BFMLG (n = 10), biomaterial and fibrin biopolymer covered by membrane and biostimulated with PBMT. The animals were euthanized at 14 and 42 days postoperatively. Microtomographically, in 42 days, there was more evident bone growth in the BFMLG, limited to the margins of the defect with permanence of the particles. Histomorphologically, an inflammatory infiltrate was observed, which regressed with the formation of mineralized bone tissue. In the quantification of bone tissue, all groups had a progressive increase in new bone tissue with a significant difference in which the BFMLG showed greater bone formation in both periods (10.12 ± 0.67 and 13.85 ± 0.54), followed by BFMG (7.35 ± 0.66 and 9.41 ± 0.84) and BMG (4.51 ± 0.44 and 7.11 ± 0.44). Picrosirius-red staining showed greater birefringence of collagen fibers in yellow-green color in the BFMLG, showing more advanced bone maturation. PBMT showed positive effects capable of improving and accelerating the guided bone regeneration process when associated with biphasic calcium phosphate and fibrin biopolymer.
Keywords: biomaterials; bone regeneration; fibrin biopolymer; low-level laser therapy; photobiomodulation therapy